2020
DOI: 10.3389/fimmu.2020.583550
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Lipopolysaccharides Suppress Erythroblastic Islands and Erythropoiesis in the Bone Marrow in an Extrinsic and G- CSF-, IL-1-, and TNF-Independent Manner

Abstract: Anemia of inflammation (AI) is the second most prevalent anemia after iron deficiency anemia and results in persistent low blood erythrocytes and hemoglobin, fatigue, weakness, and early death. Anemia of inflammation is common in people with chronic inflammation, chronic infections, or sepsis. Although several studies have reported the effect of inflammation on stress erythropoiesis and iron homeostasis, the mechanisms by which inflammation suppresses erythropoiesis in the bone marrow (BM), where differentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 85 publications
(112 reference statements)
3
18
0
Order By: Relevance
“…Based upon the preferential binding of CD169 + macrophage remnants to granulocyte populations in BM we tested and confirmed a role for CD169 in control of granulocyte egress into blood during G-CSF-induced granulopoiesis. The preferential binding of F4/80 + CD169macrophage remnants to erythroblasts is more difficult to reconcile with previous evidence (Bisht et al, 2020;Chow et al, 2013;Seu et al, 2017;Tay et al, 2020) but is consistent with in vitro experiments demonstrating that murine CD169 does not bind murine erythroblasts (Kelm et al, 1994).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Based upon the preferential binding of CD169 + macrophage remnants to granulocyte populations in BM we tested and confirmed a role for CD169 in control of granulocyte egress into blood during G-CSF-induced granulopoiesis. The preferential binding of F4/80 + CD169macrophage remnants to erythroblasts is more difficult to reconcile with previous evidence (Bisht et al, 2020;Chow et al, 2013;Seu et al, 2017;Tay et al, 2020) but is consistent with in vitro experiments demonstrating that murine CD169 does not bind murine erythroblasts (Kelm et al, 1994).…”
Section: Discussionsupporting
confidence: 62%
“…Nonetheless, we showed these ex vivo analyses can still provide valuable and robust biological information. Coupling conventional flow cytometry with in situ approaches (Kaur et al, 2018) or bespoke isolation strategies that maintain multicellular aggregates (Bisht et al, 2020;Seu et al, 2017;Tay et al, 2020;Yeo et al, 2019;Yeo et al, 2016) strengthens data interpretation, and confirms some instances of unconventional co-expression of immune markers (Abtin et al, 2014;Yates et al, 2013).…”
Section: Discussionmentioning
confidence: 54%
“…Nonetheless, we showed that these ex vivo analyses can still provide valuable and robust biological information. Coupling conventional flow cytometry with in situ approaches (Kaur et al, 2018) or bespoke isolation strategies that maintain multicellular aggregates (Bisht et al, 2020;Seu et al, 2017;Tay et al, 2020;Yeo et al, 2016Yeo et al, , 2019 strengthens data interpretation and confirms some myeloid progenitor and monocyte populations. GEO: GSE83222 (red) and GEO: GSE127980 (green) were comprised of positively selected macrophage populations.…”
Section: Discussionmentioning
confidence: 54%
“…Similar phenotypes emerge during experimental spondyloarthritis in which mice developed non-resolving inflammation [75]. In addition, consecutive injections of LPS dramatically suppressed erythropoiesis [76]. Most importantly, increasing evidence demonstrates that multiple pro-inflammatory cytokines, including IL-1β [3,4], TNF-α [42], IL-6 [4] and TGFβ1 [2], are present at increased levels in aged BM (Table 2).…”
Section: Inflammaging Of Hscmentioning
confidence: 78%